Reading Gadda, 2. Gadda’s «Giornale» and the Writings of the Great War - Giorgio Nisini (Griseldaonline, 2024)
The article aims to present a preliminary analysis of the interrelations between Carlo Emilio Gadda’s Giornale di guerra e di prigionia and the extensive textual corpus it belongs to: the autobiographical writings of the Great War. While acknowledging the originality and literary merit of the volume, which already exhibits the author’s extraordinary expressive, linguistic, and narrative qualities, the text cannot be fully apprehended without a more specific alignment with the historical circumstances in which it was conceived and elaborated, and with the vast array of testimonial writings born from the same war experience. Indeed, Gadda’s Giornale reflects a shared atmosphere and appropriates a series of recurrent topoi found throughout the memoirs of the era, albeit adapting and transforming them within the framework of a work possessing undisputed documentary and literary value.